Altered synaptic organization in the mushroom bodies of honey bees exposed as foragers to the pesticide fipronil - Privitt, James J.; Van Nest, Byron N.; Fahrbach, Susan E. (Frontiers in Bee Science, 2023)
The pesticide fipronil is a GABA receptor antagonist that induces hyperexcitability in the insect nervous system. Its use is controversial because unintentional fipronil exposure may contribute to the ongoing global decline of pollinator populations. Sublethal doses of fipronil have been tentatively linked to reduced colony fitness and impaired learning in the western honey bee, Apis mellifera. The mushroom bodies, insect brain centers important for association learning and memory, contain fipronil-sensitive receptors and may therefore be directly affected by this pesticide. We investigated the synaptic organization of the mushroom bodies in worker honey bees exposed to fipronil using immunolabeling for a pre-synaptic marker and laser scanning confocal microscopy. Exposure of honey bee foragers to fipronil at a feasible field-realistic (1 ppb) concentration decreased the estimated density of immunolabeled microglomerular synaptic complexes in the lip and collar neuropil regions of the mushroom bodies. Effects were also evident after lower (0.1 ppb) and higher (4 ppb) exposures. Other indicators of synaptic organization (bouton number, surface area) were altered by exposure to fipronil in a dose-dependent fashion. These results indicate that sublethal doses of fipronil can result in atypical synaptic organization in the mushroom bodies of honey bees and suggest a mechanism by which fipronil, through perturbation of mushroom body-dependent functions, might diminish honey bee colony survival.